HUBUNGAN PERAWATAN PAYUDARA DENGAN KELANCARAN PENGELUARAN ASI PADA IBU POST PARTUM DI DESA WONOREJO KECAMATAN TROWULAN KABUPATEN MOJOKERTO - Dewi Yanti, Ariu; Anggraeni, Liana (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Mammae’s caring was an action to caring mammae, especially in chilbed (in suckle) for ekskretion smoothness of ASI. Based on research which done at Desa Wonorejo Kecamatan Trowulan Kabupaten Mojokerto, appeared still more childbed mother that did mammae’s caring not good so that ASI’s production was not ekskretion smoothness too. As for purpose this research was to know relation between mammae’s caring and the ekskretion smoothness of ASI’s production at Desa Wonorejo Kecamatan Trowulan Kabupaten Mojokerto. Design of this research was analytic corelation survey with approximation cross sectional. The population was all childbed mother in day 4-7 as much as 12 persons, used purposive sampling technical, therefore sample which used in this reseach was 10 persons. The independence variable was mammae’s caring and dependence variable was the ekskretion smoothess of ASI’s production. Instrument which used in this research was kuesioner. The result of research show that 3 person (30%) mammae’s caring is good and ASI’s production is ekskretion smoothness 7 person (70%) than 3 person (30%) mammae’s caring isn’t good and ASI’s production isn’t ekskretion smoothness 7 person (70%). After analyzed if the meaning is relation between mammae’s caring with ekskretion smoothness of ASI’s production in childbed mother at Desa Wonorejo Kecamatan Trowulan Kabupaten Mojokerto.Keyword : Mammae’s caring, ekskretion smoothness of ASI’s production